Metal free visible light driven oxidation of alcohols to carbonyl derivatives using 3, 6-di(pyridin-2-yl)-1, 2, 4, 5-tetrazine (pytz) as catalyst. Issue 102 (5th October 2015) - Samanta, Suvendu; Biswas, Papu
Abstract : A metal-free transformation of alcohols to the corresponding carbonyls in high yields under visible-light irradiation has been achieved at room temperature using di(pyridin-2-yl)-1, 2, 4, 5-tetrazine (pytz) as catalyst. Abstract : 3, 6-Di(pyridin-2-yl)-1, 2, 4, 5-tetrazine (pytz) catalyzed oxidation of alcohols to the corresponding carbonyl compounds under visible light irradiation is described. This reaction occurs smoothly at room temperature and shows good tolerance of functional groups. It provides an alternative approach for the synthesis of alkyl and aryl aldehydes and ketones.